Glass resin laminate and manufacturing method of glass resin laminate
Patent Information
- Application Number
- JP2023142284
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0022】 本発明によれば、ガラス樹脂積層体が使用される際に重要となる温度域において、温度変化に対するヘイズ値の変化率を十分に小さくすることが可能となる。
Smart Images

Figure 2025035316000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass resin laminate having a thermoplastic adhesive layer interposed between a glass plate and a resin plate, and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art In a wide range of fields, such as cover members for various devices and building materials, glass resin laminates in which glass plates are integrally laminated on both sides of a resin plate via an adhesive layer are widely used from the viewpoint of achieving both durability and light weight.
[0003] Furthermore, in recent years, from the viewpoint of achieving further weight reduction, glass resin laminates using very thin glass sheets as the glass plates have been proposed or put into practical use (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-25152 A [Patent Document 2] JP 2014-12373 A [Patent Document 3] JP 2014-65169 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the course of long-term research, the present inventors have noticed that a conventional glass resin laminate has a large rate of change in haze value (rate of change in cloudiness) with respect to temperature change. In the course of further research, the present inventors have noticed that the rate of change in haze value with respect to temperature change is too large, particularly in a temperature range that is important when the glass resin laminate is used. The present inventors have found that when the temperature is low within the above-mentioned temperature range, the haze value becomes too large, causing the glass resin laminate to become cloudy (opaque), making it difficult to view the back side from the front side.
[0006] From the above viewpoints, an object of the present invention is to reduce the rate of change in haze value with respect to temperature change in a temperature range that is important when a glass resin laminate is used. [Means for solving the problem]
[0007] (1) A first aspect of the present invention, which has been invented to solve the above problems, is a glass resin laminate having a thermoplastic adhesive layer interposed between a glass plate and a resin plate, characterized in that, when a haze value measured in an atmosphere at a temperature of 30°C and a relative humidity of 40% in accordance with JIS K7136 (2000) is Ha%, and a haze value measured in an atmosphere at a temperature of 10°C and a relative humidity of 40% in accordance with the same standard is Hb%, Hb / Ha is 1.0 to 1.25.
[0008] According to this glass resin laminate, the rate of change of the haze value with respect to the temperature change is sufficiently small in the temperature range of 10°C to 30°C. In other words, the haze value is less likely to change in the process of changing the temperature from 30°C to 10°C compared to the conventional one. In this case, the temperature range of 10°C to 30°C corresponds to the temperature range of the interior or room where the glass resin laminate is mainly used, and therefore it can be said to be an important temperature range. Here, according to the experimental results by the present inventor, the above Hb / Ha in the conventional glass resin laminate exceeds 1.3. Therefore, in the conventional glass resin laminate, when the temperature is low within the above temperature range, the haze value becomes too large, and the glass resin laminate becomes cloudy to the extent that it is difficult to visually recognize the back side from the front side. In contrast, according to the glass resin laminate having the configuration here, since the above Hb / Ha is 1.0 to 1.25, even when the temperature is low within the above temperature range, clouding to the extent that it is difficult to visually recognize the back side from the front side is suppressed.
[0009] (2) In the above configuration (1), the haze value measured in an atmosphere having a temperature of 10° C. and a relative humidity of 40% in accordance with the above-mentioned standard may be 4.5% or less.
[0010] According to the results of experiments conducted by the present inventors, the haze value of a conventional glass resin laminate exceeded 4.5%. Therefore, the probability that the glass resin laminate would become cloudy to the extent that it would be difficult to view the back side from the front side at a temperature of about 10° C. was extremely high. In contrast, the glass resin laminate having the configuration described herein has a haze value of 4.5% or less in an atmosphere having a temperature of 10° C. and a relative humidity of 40%, so that the probability that the glass resin laminate would become cloudy to the extent that it would be difficult to view the back side from the front side at a temperature of about 10° C. is significantly reduced.
[0011] (3) In the configuration described in (1) or (2) above, the thermoplastic adhesive layer may be an adhesive layer made of EVA (ethylene-vinyl acetate thermoplastic resin).
[0012] In this way, the properties of EVA (eg, excellent transparency and adhesion) can be effectively utilized, and the above-mentioned advantages can be efficiently ensured.
[0013] Here, the present inventors have found, as a result of extensive research, that the excessively large rate of change in haze value with respect to temperature change in the temperature range of 10°C to 30°C in conventional glass resin laminates is due to the large amount of moisture contained in the thermoplastic adhesive layer. The inventions relating to the following configurations (4) to (7) were devised based on this finding. Furthermore, this finding was a factor in inducing the inventions relating to the above configurations (1) to (3).
[0014] (4) A second aspect of the present invention, which has been invented to solve the above problems, is a method for manufacturing a glass resin laminate, comprising: a lamination step of forming a temporary laminate having a sheet-like thermoplastic adhesive interposed between a glass plate and a resin plate; and a bonding step of heating the temporary laminate to bond the glass plate and the resin plate, characterized in that a drying step of drying the sheet-like thermoplastic adhesive is carried out prior to the bonding step.
[0015] According to this configuration, the moisture content of the sheet-shaped thermoplastic adhesive is reduced by performing the drying process, so that the rate of change in the haze value with respect to temperature change in the temperature range of 10°C to 30°C can be reduced. In this case, it is preferable to perform the bonding process within a short time (for example, within 2 hours) after the drying process so that the reduced moisture content in the thermoplastic adhesive does not increase again. The thermoplastic adhesive layer of the glass resin laminate obtained by performing the drying process and the bonding process is maintained in a state in which the moisture content is reduced due to the presence of the glass plate and the resin plate for a long period of time in the indoor or indoor humidity range (for example, humidity 20% to 80%) in which the glass resin laminate is mainly used. Therefore, according to this glass resin laminate, it is possible to prevent fogging to the extent that it is difficult to see from the front side to the back side for a long period of time.
[0016] (5) In the above configuration (4), the drying step may be carried out before the lamination step.
[0017] In this way, insufficient drying or poor drying of the sheet-shaped thermoplastic adhesive, which occurs when the drying step is performed after the lamination step, can be prevented.
[0018] (6) In the above configuration (4) or (5), the drying step may be performed under reduced pressure.
[0019] In this way, excessive heating of the thermoplastic adhesive is not required when performing the drying step, and therefore the thermoplastic resin adhesive can be prevented from becoming too soft due to heat and melting prior to the bonding step.
[0020] (7) In any of the above configurations (4) to (6), the drying step may be performed under reduced pressure at a temperature of 45° C. or less and a pressure of 0.1 MPa or less.
[0021] In this way, by carrying out the drying process at a temperature of 45°C or less, the sheet-shaped thermoplastic adhesive does not become too soft due to heat and melt. This allows the subsequent lamination process and adhesion process to be carried out smoothly without any problems. In addition, by carrying out the drying process at a pressure of 0.1 MPa or less, drying can be carried out efficiently. Therefore, according to this configuration, it is possible to prevent the sheet-shaped thermoplastic adhesive from melting and to reliably shorten the takt time at the same time. Effect of the Invention
[0022] According to the present invention, it is possible to sufficiently reduce the rate of change in haze value with respect to temperature change in a temperature range that is important when the glass resin laminate is used. [Brief description of the drawings]
[0023] [Figure 1] 1 is a vertical sectional front view showing a glass resin laminate according to an embodiment of the present invention. [Diagram 2] 1 is a flowchart showing a method for producing a glass resin laminate according to an embodiment of the present invention. [Diagram 3]FIG. 2 is a perspective view illustrating a preparation step in the method for producing a glass resin laminate according to the embodiment of the present invention. [Figure 4] FIG. 2 is a perspective view illustrating a drying step in the method for producing a glass resin laminate according to the embodiment of the present invention. [Diagram 5] FIG. 2 is a perspective view illustrating a lamination step in the manufacturing method of the glass resin laminate according to the embodiment of the present invention. [Figure 6] 1 is a graph for explaining an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS A glass resin laminate and a method for producing the same according to an embodiment of the present invention will now be described with reference to the accompanying drawings.
[0025] 1, in the glass resin laminate 1 according to the present embodiment, a transparent glass plate 4 is integrally laminated on each of both sides of a transparent resin plate 2 via a transparent adhesive layer 3. The glass resin laminate 1 is configured in a rectangular shape, but is not limited to this shape.
[0026] The thickness of the resin plate 2 is set to 0.01 to 20 mm, more preferably 0.05 to 15 mm, and further preferably 0.1 to 10 mm.
[0027] The material for the resin plate 2 is preferably polycarbonate, but polymethylmethacrylate resin (PMMA), polyethylene terephthalate (PET), polyether ether ketone (PEEK), polyamide (PA), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), polyethylene naphthalate (PEN), etc. may also be used.
[0028] The adhesive layer 3 is a thermoplastic adhesive layer. EVA (ethylene-vinyl acetate thermoplastic resin) is used as the material for the thermoplastic adhesive layer 3. The thickness of the adhesive layer 3 is set to 10 to 2000 μm, more preferably 50 to 1000 μm from the viewpoint of adhesive strength, and preferably 10 to 1000 μm from the viewpoint of durability.
[0029] The glass plate 4 is preferably thinner than the resin plate 2, and has a thickness of 2000 μm or less, and from the viewpoint of weight, preferably 10 to 1000 μm, and more preferably 30 to 800 μm. The thickness of the glass plate 4 is preferably thinner than the thickness of the adhesive layer 3. The thickness of the glass plate 4 may be outside the above range.
[0030] The glass plate 4 is made of silicate glass or silica glass, and preferably made of borosilicate glass, soda-lime glass, aluminosilicate glass, alkali-free glass, or the like. Here, alkali-free glass refers to glass that does not substantially contain an alkali component (alkali metal oxide), and specifically refers to glass having an alkali component weight ratio of 3000 ppm or less. In the present invention, the alkali component weight ratio is preferably 1000 ppm or less, more preferably 500 ppm or less, and further preferably 300 ppm or less.
[0031] The glass sheet 4 can be formed by a known float method, roll-out method, slot downdraw method, redraw method, etc., but is preferably formed by an overflow downdraw method. The overflow downdraw method is a method in which molten glass is poured into an overflow groove provided on the upper part of a forming body having a substantially wedge-shaped cross section, and the molten glass overflowing on both sides of the overflow groove is allowed to flow down along both side walls of the forming body and is fused and integrated at the lower end of the forming body, thereby continuously forming the glass sheets 4 one by one.
[0032] The glass resin laminate 1 consisting of the above components has a haze value measured in an atmosphere at a temperature of 30°C and a relative humidity of 40% in accordance with JIS K7136 (2000) as Ha%, and a haze value measured in an atmosphere at a temperature of 10°C and a relative humidity of 40% in accordance with the same standard as Hb%, such that Hb / Ha is 1.0 to 1.25.
[0033] According to this glass resin laminate 1, the rate of change of the haze value with respect to the temperature change is sufficiently small in the temperature range of 10°C to 30°C. In other words, according to this glass resin laminate 1, the haze value is less likely to change in the process of changing the temperature from 30°C to 10°C compared to the conventional one. In this case, the temperature range of 10°C to 30°C corresponds to the temperature range of the interior or room where this glass resin laminate 1 is mainly used, and therefore it can be said to be an important temperature range. Here, according to the results of experiments by the present inventor, the above Hb / Ha in the conventional glass resin laminate exceeds 1.3 (details will be described later). Therefore, in the conventional glass resin laminate, when the temperature is low within the above temperature range, the haze value becomes too large, and the glass resin laminate becomes cloudy (white opaque) to the extent that it is difficult to visually recognize the back side from the front side. In contrast, according to this glass resin laminate 1, since the above Hb / Ha is 1.0 to 1.25, it is possible to prevent the clouding to the extent that it is difficult to visually recognize the back side 6 from the front side 5, even when the temperature is low within the above temperature range. The above Hb / Ha is more preferably 1.0 to 1.15, and even more preferably 1.0 to 1.10.
[0034] Moreover, the glass resin laminate 1 has a haze value of 4.5% or less when measured in an atmosphere at a temperature of 10° C. and a relative humidity of 40% in accordance with the JIS K7136 (2000) standard.
[0035] According to the results of experiments by the present inventors, the haze value of a conventional glass resin laminate exceeded 4.5% (details will be described later), and therefore the probability of the glass resin laminate becoming cloudy to such an extent that it becomes difficult to visually recognize the back side from the front side at a temperature of about 10° C. was extremely high. In contrast, according to the glass resin laminate 1, the haze value measured in accordance with the JIS K7136 (2000) standard in an atmosphere of a temperature of 10° C. and a relative humidity of 40% is 4.5% or less, and therefore the probability of the glass resin laminate 1 becoming cloudy to such an extent that it becomes difficult to visually recognize the back side 6 from the front side 5 at a temperature of about 10° C. is significantly reduced. The haze value is more preferably 4.0% or less, and even more preferably 3.7% or less.
[0036] Next, a method for manufacturing the glass resin laminate 1 having the above-mentioned configuration will be described. As shown in Fig. 2, the manufacturing method includes a preparation step S1, a drying step S2, a lamination step S3, and a bonding step S4.
[0037] In the preparation step S1, as shown in FIG. 3, one resin plate 2, two glass plates 4, and two sheet-like adhesives 3a are prepared.
[0038] In the drying step S2, as shown in Fig. 4, the two sheet-like adhesives 3a prepared in the preparation step S1 are taken out and each of these adhesives 3a is dried by vacuum drying. Each of these adhesives 3a is a thermoplastic adhesive made of EVA (ethylene-vinyl acetate thermoplastic resin), and becomes the adhesive layer 3 of the glass resin laminate 1 described above by carrying out the drying step S2, lamination step S3, and adhesion step S4.
[0039] In the drying step S2, more specifically, each of the two sheet-like adhesives 3a is dried under reduced pressure at a temperature of 45° C. or less and a pressure of 0.1 MPa or less.
[0040] In this case, if the drying process is performed at a temperature exceeding 45°C, the sheet-like adhesive 3a may become too soft due to heat and melt, which may cause problems in the subsequent lamination process S3 and adhesion process S4, or may cause a deterioration in the quality of the glass resin laminate 1. Specifically, if the sheet-like adhesive 3a melts, the thickness of the sheet becomes uneven, and as a result, the adhesiveness of the adhesive 3a becomes uneven, and the glass plate 4 may become easily peeled off. In addition, if the drying process is performed at a pressure exceeding 0.1 MPa, there is a risk that the drying may not be efficient. On the other hand, these problems do not occur in the above-mentioned reduced pressure drying. Therefore, according to the above-mentioned reduced pressure drying, it is possible to prevent the sheet-like adhesive 3a from melting and to sufficiently shorten the takt time at the same time.
[0041] Furthermore, the weight loss rate of the sheet-like adhesive 3a due to the drying step S2 is preferably 0.1% or more. Here, the weight loss rate is calculated by (W1-W2) / W1(%), where W1 is the weight of the sheet-like adhesive 3a before the drying step S2 and W2 is the weight of the sheet-like adhesive 3a after the drying step S2. This weight loss rate is considered to be due to a decrease in the moisture content of the sheet-like adhesive 3a.
[0042] As described above, the drying step S2 reduces the amount of moisture contained in the sheet-like adhesive 3a, thereby reducing the rate of change in the haze value relative to temperature changes in the temperature range of 10° C. to 30° C. The adhesive layer 3 of the glass resin laminate 1 obtained by carrying out the lamination step S3 and bonding step S4 after the drying step S2 maintains a state in which the amount of moisture is reduced for a long period of time due to the presence of the glass plate 4 and the resin plate 2 in the indoor or room humidity range (e.g., humidity 20% to 80%) where the glass resin laminate 1 is mainly used. Therefore, the obtained glass resin laminate 1 can be prevented from fogging for a long period of time to the extent that it becomes difficult to view the back surface 6 side from the front surface 5 side.
[0043] In the lamination step S3, as shown in Fig. 5, the resin plate 2 prepared in the preparation step S1, two sheet-like adhesives 3a that have been dried in the drying step S2, and two glass plates 4 prepared in the preparation step S1 are stacked together to form a temporary laminate 1a. The drying step S2 is performed before the lamination step S3, thereby preventing insufficient drying or poor drying of the sheet-like adhesives 3a.
[0044] In the bonding step S4, the temporary laminate 1a formed in the lamination step S3 is heated. More specifically, in the bonding step S4, the temporary laminate 1a is bonded by thermocompression bonding, for example, using an autoclave. As a result, the sheet-like adhesive 3a is softened to form an adhesive layer 3, which integrates the resin plate 2 and the glass plate 4. In this case, it is preferable that the time from the end of the drying step S2 to the execution of the bonding step S4 is short (for example, within 2 hours). In this way, the moisture content of the adhesive 3a, which has decreased due to the execution of the drying step S2, is prevented from increasing again. Then, at the time when the bonding step S4 is completed, the glass resin laminate 1 shown in FIG. 1 is obtained. EXAMPLES
[0045] The inventors manufactured four types of glass resin laminates 1 by carrying out the above-mentioned preparation step S1, drying step S2, lamination step S3, and bonding step S4. The four types of glass resin laminates 1 have different weight reduction rates (moisture reduction rates) of the sheet-shaped adhesive 3a obtained by carrying out the drying step S2. The first glass resin laminate 1 (Example 1) has a moisture reduction rate of 0.10%, the second glass resin laminate 1 (Example 2) has a moisture reduction rate of 0.12%, and the third glass resin laminate 1 (Example 3) has a moisture reduction rate of 0.13%. In this case, in the drying step S2, all of Examples 1 to 3 were subjected to reduced pressure drying at a temperature of 45°C or less (here, 30°C) and a pressure of 0.1 MPa or less (here, 80 Pa) for 120 minutes. Then, after the reduced pressure drying, the bonding step S4 was carried out 30 minutes later. For the fourth glass resin laminate 1 (comparative example), the drying step S2 was not performed on the sheet-like adhesive 3a, and the moisture loss rate was 0.00. The haze values of these four types of glass resin laminates 1 were measured at temperatures of 10°C, 20°C, 30°C, and 40°C. The relative humidity during the measurements was 40%. All of the haze values were measured in accordance with the JIS K7136 (2000) standard.
[0046] The above measurement results are shown in the graph of FIG. 6 and Table 1 below. In FIG. 6, Example 1 (moisture reduction rate: 0.10) is shown by a dashed line curve L1, and the measurement points from 10°C to 40°C are shown as A to D, respectively. In addition, in the same figure, Example 2 (moisture reduction rate: 0.12) is shown by a dotted line curve L2, and the measurement points from 10°C to 40°C are shown as E to H, respectively. Furthermore, in the same figure, Example 3 (moisture reduction rate: 0.13) is shown by a solid line curve L3, and the measurement points from 10°C to 40°C are shown as I to L, respectively. In contrast, in the same figure, Comparative Example (moisture reduction rate: 0.00) is shown by a two-dot dashed line curve Lx, and the measurement points from 10°C to 40°C are shown as M to P, respectively.
[0047] The following Table 1 shows, as numerical values, the haze values (%) of each of A to D in Example 1, the haze values (%) of each of E to H in Example 2, the haze values (%) of each of I to L in Example 3, and the haze values (%) of each of M to P in the comparative example. Note that each of these haze values is an average value calculated based on the haze values (%) of 10 pieces of each of the four types of glass resin laminates 1 manufactured. [Table 1]
[0048] According to the graph in FIG. 6 and Table 1 above, in all of Examples 1 to 3 and Comparative Example, the haze values at 40° C. are in the range of 2.42 to 2.49, and the respective haze values are small and very close to each other. In contrast, in Examples 1 to 3, the haze value increases as the temperature changes from 30° C. to 10° C., but the rate of increase is small. In other words, the rate of change in the haze value is small. On the other hand, in the Comparative Example, the rate of increase in the haze value increases significantly as the temperature changes from 30° C. to 10° C. In other words, the rate of change in the haze value is extremely large.
[0049] According to Table 1 above, the largest haze value at a temperature of 10°C among Examples 1 to 3 is 4.23% in Example 1, which is significantly lower than 4.5%. In contrast, the haze value at a temperature of 10°C in the comparative example is 4.83%, which is significantly higher than 4.5%. Thus, when the haze value at a temperature of 10°C is 4.5% or less, it is possible to prevent the glass resin laminate 1 from fogging to such an extent that it becomes difficult to visually recognize the back surface 6 side from the front surface 5 side. Moreover, the haze value at a temperature of 10°C in Example 2 is 3.82%, and the haze value at a temperature of 10°C in Example 3 is 3.61%, which allows for efficient fogging.
[0050] Also, referring to Table 1 above, in Example 1, the haze value C at a temperature of 30° C. is 3.43%, and the haze value A at a temperature of 10° C. is 4.23%, so A / C is 1.23. In Example 2, the haze value G at a temperature of 30° C. is 3.53%, and the haze value E at a temperature of 10° C. is 3.82%, so E / G is 1.08. In Example 3, the haze value K at a temperature of 30° C. is 3.33%, and the haze value I at a temperature of 10° C. is 3.61%, so I / K is 1.08. In contrast, in the comparative example, the haze value O at a temperature of 30° C. is 3.67%, and the haze value M at a temperature of 10° C. is 4.83%, so M / O is 1.32.
[0051] Although an embodiment of the present invention has been described above, the embodiment of the present invention is not limited to this, and various modifications are possible without departing from the gist of the present invention.
[0052] For example, in the above embodiment, the glass resin laminate 1 is formed by laminating and integrating the glass plate 4 on both sides of the resin plate 2 via an adhesive layer 3, but the glass plate 4 may be laminated and integrating on only one side of the resin plate 2 via an adhesive layer 3.
[0053] In the above embodiment, one adhesive layer 3 is interposed between the glass plate 4 and the resin plate 2, but two or more adhesive layers 3 may be interposed. In this case, it is preferable that each of the two or more adhesive layers 3 is dried under reduced pressure in the drying step S2.
[0054] In the above embodiment, an adhesive made of EVA is used as the thermoplastic adhesive 3a, but an adhesive made of, for example, PVA (polyvinyl alcohol) may also be used.
[0055] In the above embodiment, the adhesive 3a is dried under reduced pressure in the drying step, but it may be dried without reducing pressure.
[0056] In the above embodiment, the drying step S2 is performed before the lamination step S3, but it may be performed after the lamination step S3 and before the adhesion step S4.
[0057] In the above embodiment, the resin plate 2, the adhesive layer 3, and the glass plate 4 are transparent, but this “transparency” does not mean that these 2, 3, and 4 need not be colorless and transparent; at least one of these 2, 3, and 4 may be colored. [Explanation of symbols]
[0058] 1 Glass-resin laminate 1a Temporary laminate 2 Resin plate 3 Adhesive layer (thermoplastic adhesive layer) 3a Adhesive (thermoplastic adhesive) 4 Glass Plate 5. Surface of glass-resin laminate 6 Back side of glass resin laminate S2 Drying process S3 Lamination process S4 Adhesion process
Claims
1. A glass resin laminate having a thermoplastic adhesive layer interposed between a glass plate and a resin plate, When the haze value measured in an atmosphere at a temperature of 30° C. and a relative humidity of 40% in accordance with the standard of JIS K7136 (2000) is Ha%, and the haze value measured in an atmosphere at a temperature of 10° C. and a relative humidity of 40% in accordance with the same standard is Hb%, A glass resin laminate, characterized in that Hb / Ha is 1.0 to 1.
25.
2. 2. The glass resin laminate according to claim 1, wherein the haze value measured in an atmosphere at a temperature of 10° C. and a relative humidity of 40% in accordance with the above-mentioned standard is 4.5% or less.
3. 3. The glass resin laminate according to claim 1, wherein the thermoplastic adhesive layer is an adhesive layer made of EVA (ethylene-vinyl acetate thermoplastic resin).
4. A method for producing a glass resin laminate, comprising: a lamination step of forming a temporary laminate in which a sheet-like thermoplastic adhesive is interposed between a glass plate and a resin plate; and a bonding step of heating the temporary laminate to bond the glass plate and the resin plate, A method for producing a glass resin laminate, comprising the steps of: prior to the bonding step, carrying out a drying step of drying the sheet-like thermoplastic adhesive;
5. The method for producing a glass resin laminate according to claim 4 , wherein the drying step is carried out before the laminating step.
6. The method for producing a glass resin laminate according to claim 4 or 5, characterized in that in the drying step, drying under reduced pressure is performed.
7. 7. The method for producing a glass resin laminate according to claim 6, wherein in the drying step, drying is performed under reduced pressure at a temperature of 45° C. or lower and a pressure of 0.1 MPa or lower.
Citation Information
Patent Citations
Glass film laminate
JP2012025152A
Glass resin laminate
JP2014012373A
Glass film laminate for display object cover
JP2014065169A